Alinhamento e estratégias de relativização - Camacho, Roberto Gomes [UNESP] (FapUNIFESP (SciELO), 2017)
This paper aims at examining the hypothesis that the choice among the different strategies of relativization available in Portuguese grammar is motivated by a lesser or greater degree of transparency between form and meaning correlating with a lesser or greater degree of ease in cognitive processing. In addition, the different degrees of transparency allow the postulation of a hierarchical ordering of the strategies in correspondence with different degrees of ease in cognitive processing. This hypothesis is based on the principle postulated by Comrie (1989), which states that if a language has a more explicit relativization strategy and a less explicit one, the more explicit type would be used to relativize the lower positions on a scale of grammatical relations and the less explicit type would be used to relativize the highest ones. A concept that fi ts well to this principle is alignment, postulated by Hengeveld and Mackenzie (2008) to represent the way pragmatic and semantic units, which are not hierarchically related, map onto morphossyntactic and phonological units; in other terms, the way the encoding process refl ect the motivations of the formulation process.
Alignment and relativization strategies
Keywords: Economy; Iconicity; Opacity; Relative construction; Transparency